2012
DOI: 10.1152/ajplung.00128.2012
|View full text |Cite
|
Sign up to set email alerts
|

Acute cigarette smoke exposure impairs proteasome function in the lung

Abstract: Cigarette smoke mediates DNA damage, lipid peroxidation, and modification and misfolding of proteins, thereby inducing severe cellular damage. The ubiquitin proteasome system serves as the major disposal system for modified and misfolded proteins and is thus essential for proper cellular function. Its role in cigarette smoke-induced cell damage, however, is largely unknown. We hypothesized that the ubiquitin-proteasome system is involved in the degradation of cigarette smoke-damaged proteins and that cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 37 publications
9
83
1
1
Order By: Relevance
“…We therefore assessed the role of HDAC6 in protein aggregation and clearance after CS exposure. CS, a potent prooxidant agent, is known to alter protein homeostasis by causing the oxidative modification of proteins, the disruption of protein folding, as well as altered protein processing in the ER, leading to the formation of protein aggregates (7)(8)(9). Consequently, protein aggregates may be solubilized by protein chaperones and removed by proteosomal degradation, or organized in centralized aggresomes and removed by the autophagic pathway (50).…”
Section: Cs-induced Autophagic Processing Of Ubiquitinated Proteins Imentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore assessed the role of HDAC6 in protein aggregation and clearance after CS exposure. CS, a potent prooxidant agent, is known to alter protein homeostasis by causing the oxidative modification of proteins, the disruption of protein folding, as well as altered protein processing in the ER, leading to the formation of protein aggregates (7)(8)(9). Consequently, protein aggregates may be solubilized by protein chaperones and removed by proteosomal degradation, or organized in centralized aggresomes and removed by the autophagic pathway (50).…”
Section: Cs-induced Autophagic Processing Of Ubiquitinated Proteins Imentioning
confidence: 99%
“…The mechanisms underlying CS-induced epithelial cell injury and dysfunction remain unclear, but may include a protease/antiprotease imbalance, inflammation, oxidative stress, and programmed cell death (2)(3)(4). Recent studies have suggested additional pathway mechanisms involving altered protein homeostasis (proteostasis) (5,6), including ER stress, inhibition of the ubiquitin-proteasome system (7)(8)(9), and autophagy (10)(11)(12)(13), all of which potentially contribute to the pathogenesis of chronic lung diseases and emphysema (5).…”
Section: Introductionmentioning
confidence: 99%
“…of cystic fibrosis transmembrane conductance regulator (CFTR), which may also contribute to COPD pathogenesis [70][71][72][73][74][75]. Of note, the proteasome itself is a direct target for environmental challenges as cigarette smoke and diesel exhaust have been shown to impair proteasome function [76,77]. In accordance with that observation, proteasome function is reduced in lungs of COPD patients and in mouse models of chronic cigarette exposure, which correlates inversely with the loss of lung function [79].…”
Section: Loss Of Proteostasismentioning
confidence: 95%
“…Hence, it is highly likely that CS and aging modulate a common process, such as proteostasis, that can affect multiple cellular pathways to promote COPD-emphysema pathogenesis (15). In fact, CS and age-related proteostasis imbalance are known to modulate proteasomal degradation (13,14,21,22), which can induce accumulation of ubiquitinated proteins as aggresome bodies. Aggresomes are insoluble clusters of ubiquitinated proteins that are formed as a cellular response mechanism to decreased proteasomal activity (23)(24)(25)(26)(27).…”
Section: Clinical Relevancementioning
confidence: 99%